Identification of Two Subsets of Murine DC1 Dendritic Cells That Differ by Surface Phenotype, Gene Expression, and Function - Hongo, David; Zheng, Pingping; Dutt, Suparna; Pawar, Rahul D.; Meyer, Everett; Engleman, Edgar G.; Strober, Samuel (Frontiers in Immunology, 2021)
Classical dendritic cells (cDCs) in mice have been divided into 2 major subsets based on the expression of nuclear transcription factors; a CD8+Irf8+Batf3 dependent (DC1) subset, and a CD8-Irf4+ (DC2) subset. We found that the CD8+DC1 subset can be further divided into CD8+DC1a and CD8+DC1b subsets by differences in surface receptors, gene expression, and function. Whereas all 3 DC subsets can act alone to induce potent Th1 immune responses to class I and II MHC restricted peptides derived from ovalbumin (OVA) by OT-I and OT-II transgenic T cells, only the DC1b subset could effectively present glycolipid antigens to natural killer T (NKT) cells. Vaccination with OVA protein pulsed DC1b and DC2 cells were more effective in reducing the growth of the B16-OVA melanoma as compared to pulsed DC1a cells in wild type mice. In conclusion, the Batf3-/- dependent DC1 cells can be further divided into two subsets with different immune functional profiles in vitro and in vivo.